Factors affecting the success of highway construction projects: The case of Malaysia - A. R., Rahimi; A. R., Radzi; M. S. H., Saad; Doh, Shu Ing (IOP Publishing, 2020)
Highways are often high-risk projects due to its importance to a nation’s economic, societal, and political development. Therefore, highway projects need to be successful. Numerous researchers have identified the key factors affecting their local highway projects to identify opportunities for improvements. However, the current body of literature lacks that type of information in regards to Malaysia’s construction industry. This study’s objective is to identify factors that are affecting Malaysia’s highway projects from industry practitioners’ perspective. To achieve this objective, interview data with highway project managers are analyzed. Eleven factors affecting the success of highway projects in Malaysia were identified. The factors are: workflow for the design process, competencies of project managers, availability of workforce, availability of materials, availability of equipment, weather, site location, involvement from upper management, support from clients, public acceptance, and efficiency of authorities. This study contributes to the current body of knowledge by providing researchers and practitioners with a set of alternative factors that are affecting highway project success. The lesson of this study would help the industry to promote project success of highway projects in Malaysia.